Assessing the Structural and Alteration Controls on Gold Mineralization at Detour Lake Mine, Ontario, Canada - Dubosq, Renelle (Université d'Ottawa / University of Ottawa, 2017)
The giant Detour Lake deposit is a Neoarchean orogenic Au ore body located in the northwestern Abitibi district within the Superior Province. The deposit is situated along the high strain Sunday Lake Deformation Zone (SLDZ) parallel to the broadly E-W trending Abitibi greenstone belt. The lower amphibolite facies assemblage (Act-Bt-Pl-Ep-Alm ±Cal ±Qz ±Ilm) suggests maximum temperatures reaching 550°C, exceeding conditions for pyrite plasticity, an important and ubiquitous Au-bearing phase that may ultimately represent the source for Au at orogenic style Au deposits. The metamorphic assemblage also obscures the relationship between Au and biotite, a visual indicator mineral within Au-rich ore zones. This work combines microstructural, geochemical and geochronological analyses to assess the influence of regional scale deformation and alteration on Au mineralization. EBSD and LA-ICP-MS analyses on pyrite reveal Au enrichment at microstructures supporting a syn- to post-peak metamorphic and deformation-assisted Au upgrading model. EMPA and 40Ar/39Ar analyses on biotite reveal one chemically homogeneous population, which yield variably reset ages that post-date regional metamorphism and Au mineralization.
Keywords: pyrite; EBSD; LA-ICP-MS; diffusion